Antimicrobial Activity of Eucalyptus globulus, Azadirachta indica, Glycyrrhiza glabra, Rheum palmatum Extracts and Rhein against Porphyromonas gingivalis - Lena Katharina Müller-Heupt; Nina Vierengel; Jonathan Groß; Till Opatz; James Deschner; Friederike D. von Loewenich (MDPI AG, 2022)
Novel plant-derived antimicrobials are of interest in dentistry, especially in the treatment of periodontitis, since the use of established substances is associated with side effects and concerns of antimicrobial resistance have been raised. Thus, the present study was performed to quantify the antimicrobial efficacy of crude plant extracts against Porphyromonas gingivalis, a pathogen associated with periodontitis. The minimal inhibitory concentrations (MICs) of Eucalyptus globulus leaf, Azadirachta indica leaf, Glycyrrhiza glabra root and Rheum palmatum root extracts were determined by broth microdilution for P. gingivalis ATCC 33277 according to CLSI (Clinical and Laboratory Standards Institute). The MICs for the E. globulus, A. indica and G. glabra extracts ranged from 64 mg/L to 1024 mg/L. The lowest MIC was determined for an ethanolic R. palmatum extract with 4 mg/L. The MIC for the anthraquinone rhein was also measured, as the antimicrobial activity of P. palmatum root extracts can be partially traced back to rhein. Rhein showed a remarkably low MIC of 0.125 mg/L. However, the major compounds of the R. palmatum root extract were not further separated and purified. In conclusion, R. palmatum root extracts should be further studied for the treatment of periodontitis.